2016
DOI: 10.1002/ece3.1964
|View full text |Cite
|
Sign up to set email alerts
|

Leaf economics spectrum–productivity relationships in intensively grazed pastures depend on dominant species identity

Abstract: Plant functional traits are thought to drive variation in primary productivity. However, there is a lack of work examining how dominant species identity affects trait–productivity relationships. The productivity of 12 pasture mixtures was determined in a 3‐year field experiment. The mixtures were based on either the winter‐active ryegrass (Lolium perenne) or winter‐dormant tall fescue (Festuca arundinacea). Different mixtures were obtained by adding forb, legume, and grass species that differ in key leaf econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…Instances where the more diverse mixture performs better could be due either to niche complementarity or positive selection effects. A previous study showed that adding the winter dormant forbs chicory and plantain to ryegrass–white clover mixtures enhances mean productivity due to their phenological (seasonal) complementarity with winter‐active ryegrass (Mason et al., ), suggesting there may be some potential for niche complementarity to enhance productivity even in intensively managed agricultural ecosystems. Other studies have emphasized the potential for increased diversity to enhance productivity through complementarity in nitrogen resource use between legumes and non‐N‐fixers (e.g., Nyfeler, Huguenin‐Elie, Suter, Frossard, & Lüscher, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instances where the more diverse mixture performs better could be due either to niche complementarity or positive selection effects. A previous study showed that adding the winter dormant forbs chicory and plantain to ryegrass–white clover mixtures enhances mean productivity due to their phenological (seasonal) complementarity with winter‐active ryegrass (Mason et al., ), suggesting there may be some potential for niche complementarity to enhance productivity even in intensively managed agricultural ecosystems. Other studies have emphasized the potential for increased diversity to enhance productivity through complementarity in nitrogen resource use between legumes and non‐N‐fixers (e.g., Nyfeler, Huguenin‐Elie, Suter, Frossard, & Lüscher, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another consideration is the difficulty in maintaining diversity in pasture mixtures. A previous study of intensively managed grazed pastures showed that the abundance of chicory, plantain, and lucerne had declined markedly after 3 years (Mason et al, 2016). The requirements of intensive pastoral agriculture-the ability to produce large amounts of high-quality herbage while tolerating frequent defoliation and trampling-place severe constraints on the pool of viable species (Finn et al, 2013).…”
Section: Could Diversity Increase Agricultural Certainty In Increasmentioning
confidence: 99%
“…We measured traits related to plant growth strategies (leaf dry matter content [LDMC], leaf N, leaf thickness, specific root length [SRL], root tissue density [RTD] and root diameter) and water use efficiency or uptake (δ 13 C, root diameter) (Bardgett et al., ; Perez‐Harguindeguy et al., ; Reich, ), each of which may influence soil functioning through modifying the quality or quantity of inputs. Leaf traits were measured in spring only (Mason et al., ; Table ), using standard techniques (Perez‐Harguindeguy et al., ). Leaf δ 13 C was measured using a Europa Scientific 20‐20 Stable Isotope Analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…Leaf trait diversity has also been shown to influence productivity, decomposition and N retention in these systems (Grigulis et al, 2013;Mouillot et al, 2011;Scherer-Lorenzen, 2008). Although there is some evidence that plant productivity may be influenced by leaf traits in intensively grazed systems (Mason et al, 2016), frequent grazing reduces the opportunities for leaf litter to enter the soil and therefore to influence soil C and nutrient cycling. Fertiliser and high-N grazer urine inputs may further reduce the ability of plants to influence nutrient cycling (Orwin et al, 2015;Soussana & Lemaire, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation